VvMYB15 and VvWRKY40 Positively Co-regulated Anthocyanin Biosynthesis in Grape Berries in Response to Root Restriction - Li, Dongmei; Wang, Zhenping; Sun, Sijie; Xiao, Kun; Cao, Minghao; Li, Xiangyi; Ma, Chao; Zhang, Caixi; Wang, Lei; Lian, Hongli; Wang, Shiping (Frontiers in Plant Science, 2021)
In most grapevine planting regions, especially in south of china, plenty of rainfall and high water level underground are the characteristic of the area, a series of problem during fruit ripening easily caused poor color quality. Thereby affecting fruit quality, yield and economic benefits. Anthocyanin accumulation is regulated by transcriptional regulatory factor and a series of cultivation measures, root restriction can make plants in the environment of stress and stress relief, root restriction induced the higher expression of VvMYB15 and VvWRKY40 and consistent with anthocyanin accumulation. Whether and how root restriction-inducible VvMYB15 and VvWRKY40 transcription factor regulate anthocyanin synthesis in grape berry is still unclear. In this study, we identified that the transient overexpression of VvMYB15 and VvWRKY40 alone or both in strawberry fruits and grape berries can promote anthocyanin accumulation and increase the expression level of anthocyanin biosynthetic genes, indicating VvMYB15 and VvWRKY40 play a positive regulator of anthocyanin biosynthesis. Furthermore, we confirmed that both VvMYB15 and VvWRKY40 specifically bind to the promoter region of VvF3’5’H and VvUFGT, and the expression of VvF3’5’H and VvUFGT was further activated through the heterodimer formation between VvMYB15 and VvWRKY40. Finally, we confirmed that VvMYB15 promoted anthocyanin accumulation by interacting with VvWRKY40 in grape berries, our findings provide insights into a mechanism involving the synergistic regulation of root restriction-dependent coloration and biosynthesis via a VvMYB15 and VvWRKY40 alone or both in grape berries.